Investigating the roles of the floral-associated genes TRIPTYCHON, SHATTERPROOF and AGAMOUS in Arabidopsis thaliana and Brassica rapa - Breathnach, Caoilfhionn (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2024)
The genetic mechanisms responsible for flower development has been studied for over four decades now in Arabidopsis thaliana, a model organism for plants. However, more recently, plant research has become increasingly focused on additional species, and the translation of knowledge gained through studying Arabidopsis into other species used in agriculture. Through a combination of basic and translational research, in this thesis I sought to gain a deeper understanding of the development and regulation of the gynoecium in the family Brassicaceae. The first results section of the thesis investigates the role of the trichome repressor TRIPTYCHON (TRY) in the establishment of the replum in the gynoecium of Arabidopsis thaliana. This work emerged from previous observations within our lab. Until now, loss-of-function mutant lines of triptychon have been studied primarily in relation to the trichome clustering phenotype observed. The aim of this project was to independently assess the previous observation that try mutant plants also have a narrow replum, which was thought to be hypersensitive to exogenous cytokinin treatment. I developed a protocol for accurately measuring repla in large sample sizes to facilitate reproducing this observation. Novel try mutant lines were generated in this study using CRISPR/Cas9 genome editing, as well as complementation experiments to rescue the replum phenotype by reintroducing TRY activity. This was done to ascertain if the replum phenotype observed was a result of the loss of TRY function as opposed to any other artefact in the genetic background of the try-29760 allele. Finally, through generating double mutants combining try-29760 and other mutants carrying replum defects, as well as RT-qPCR analyses, I successfully identified co-factors of TRY in replum patterning. Through this work, a novel function of TRY in promoting replum formation was characterised, which seems to have evolved independently of the trichome formation machinery that it is normally associated with in the literature to date. Additionally, some interactors of TRY within the gynoecium patterning gene regulatory network were identified, namely RE- PLUMLESS and ASYMMETRIC LEAVES1. Understanding the genetic regulation of developmental processes is highly important when seeking to increase the resistance of plants to common environmental stresses, such as drought and herbivory. This can be achieved by exploiting these genetic pathways to our advantage. A critical area of plant research is investigating methods of increasing and preserving yield. In Brassica rapa var. Yellow Sarson, the fruit is the most economically important organ of the plant, as the seeds are required to produce oil. Developing a method of protecting these crops from seed loss could potentially be a hugely beneficial addition to agriculture. The next section of the thesis sought to identify the homologs of the Arabidopsis SHATTERPROOF1 & 2 in Brassica rapa, as they could be targeted to minimise seed loss. The aim of this work was to translate established work completed in Arabidopsis thaliana to the more agronomically valuable species Brassica rapa. Shatter resistance on the seed pod of Brassica rapa could protect them from opening due to weather conditions, thus preserving seed yield when they are harvested. Four homologs were identified by sequence and synteny analyses. After identifying the homologs, they were functionally characterised by RT-qPCR experiments to illustrate the expression domains of these genes. This found that, while Arabidopsis thaliana SHP1/2 is exclusively expressed in the gynoecium, the B. rapa homologs are also expressed in the stamens. Complementation experiments were then carried out in Arabidopsis thaliana, which demonstrated that these identified genes were indeed true homologs of SHAT- TERPROOF1/2 as well as exploring the differences in expression domains across the two species. 3’ RACE PCR allowed for the identification of the 3’ UTR of each of the four genes in order to isolate unique segments of each of them. Additionally, TILLING mutant lines for each of these four homologs were acquired and higher-order mutants were subsequently generated. The pod shatter resistance of these mutant lines was quantified through the use of a random impact test. This revealed that even in a double mutant combination, the pod shatter resistance is increased when compared to the wild type. Leading on from this work in Brassica rapa, the final section of the thesis examines the redundancy of the MADS box transcription factors AGAMOUS (AG) and SHATTERPROOF1 & 2 (SHP1/2) in the repression of trichome initiation on the gynoecium in the family Brassicaceae. It was previously shown in Ó Maoiléidigh et al. (2018) that the phenotype of ag try-29760 cpc-1 triple mutants in Arabidopsis - with trichomes on their gynoecia - is exacerbated in a shp1/2 mutant background and can be partially rescued by introducing SHP2 overexpression, suggesting that AG and SHP2 are at least partially redundant in repressing trichome initiation on the gynoecium. To combine the use of basic and translational research approaches, I endeavoured to further investigate this re- dundancy in Arabidopsis thaliana, before investigating the functional redundancy of AG and SHP genes identified in Brassica rapa. To do this, I generated higher order mutants in Arabidopsis and assessed their phenotypes, as well as examining the effect of exogenous cytokinin treatment, which is known to promote trichome initiation. Furthermore, I tested the function of the large intron in BrSHP2 as a promoter, due to the large intron of AtAG being required for normal expression. This demonstrated that the large intron of BrSHP2 does indeed function as a promoter. This suggests that BrSHP2 may be more functionally similar to AtAG than AtSHP2 is.
N/A
APPROVED
Keywords: Genetics; Plant; Development; Gynoecium; Arabidopsis; Brassica; Shatterproof; Triptychon; Flower